THE INFLUENCE OF ENVIRONMENTAL FACTORS ON THE VARIABILITY OF TEENAGERS HEART RHYTHM - S. Ye. Shvayko; O. R. Dmytrotsa; O. A. Zhuravlov; O. O. Zacharchuk (Vіsnik Naukovih Doslіdžen', 2018)
The intense environmental pollution that has been observed over the last decade leads to the deterioration in health of modern schoolchildren living in different territories, due to the environmental factors, areas. Anthropogenic stresses lead to more intensive use of organism adaptive possibilities. It responds to the effects of adverse factors in the teenagers’ body due to incomplete morphological and functional development. An indicator of the functional status of the body of children and teenagers is the characteristic of heart rate variability (HRV). Heart rate (HR) responds to all the factors of the environment, reflecting the growth and development of the organism during ontogeny. It leads to the need for a more thorough study of HRV, which is one of the available non-invasive methods to determine the state of the cardiovascular system.